Agricultural Economic Performance, Fraud-Prevention Governance, And Environmental Quality - Simanjuntak, Barita (Sam Ratulangi University, 2026)
Agricultural development plays an important role in regional economic growth, rural livelihoods, food security, and natural resource management. However, agricultural performance varies across regions and should be interpreted together with governance and environmental considerations. This article analyzes agricultural economic performance, fraud-prevention governance, and environmental quality across regencies and municipalities in Central Sulawesi Province, Indonesia. A quantitative descriptive approach with comparative regional analysis was applied using verified secondary data from official government sources. Agricultural economic performance was measured using the gross regional domestic product of the agriculture, forestry, and fisheries sector, while fraud-prevention governance and environmental quality were discussed based on available official information related to the Monitoring Center for Prevention framework and the Environmental Quality Index. The results show substantial spatial variation in agricultural economic performance. In 2024, agricultural GRDP ranged from IDR 1,241.27 billion in Kota Palu to IDR 9,969.49 billion in Parigi Moutong, with a mean of IDR 4,565.74 billion and a standard deviation of IDR 2,585.52 billion. Parigi Moutong and Banggai were classified as high-performing regions based on normalized agricultural GRDP scores, while Donggala, Sigi, Morowali Utara, Poso, and Tolitoli were classified as medium-performing regions. The findings also indicate that agricultural importance differs between absolute agricultural GRDP and agricultural share in total GRDP. Banggai Laut recorded the highest agricultural share at 55.84%, whereas Morowali had the largest total GRDP but only 1.55% agricultural share. These patterns suggest that sustainable agribusiness policy in Central Sulawesi should be regionally differentiated. Areas with large agricultural economies require value-chain strengthening and agro-processing, while areas with high agricultural dependence need productivity improvement, farmer welfare support, rural infrastructure, and market connectivity. The limited availability of verified district-level MCP/MCSP and IKLH data remains a constraint, highlighting the need for more complete local governance and environmental datasets for future correlation and composite-index analysis. Keywords: Agricultural economy; Central Sulawesi; Environmental quality; Fraud prevention; Sustainable agribusiness